HUBUNGAN KEMAMPUAN LITERASI SEJARAH DAN RASIONALITAS KOMUNIKATIF SISWA DALAM MERESPON ISU-ISU SEJARAH KONTEMPORER DI SMK ADHIKAWACANA SURABAYA KELAS XI - Fika Anggreini; Agus Suprijono (STKIP Subang, 2026)
This study aims to examine the relationship between historical literacy skills and students' communicative rationality in responding to contemporary historical issues at SMK Adhikawacana Surabaya. This study used a quantitative approach with a correlational research method. The study respondents included 34 grade XI Office Management 1 students selected using a purposive sampling technique. Data collection was conducted using a descriptive test based on the Solo Taxonomy to measure students' historical literacy and communicative rationality. The research instrument underwent validity and reliability testing before use. Data analysis was conducted using descriptive statistics, prerequisite analysis tests, Pearson Product Moment correlation, and simple linear regression. The results showed a positive and significant relationship between historical literacy and students' communicative rationality. The findings indicate that the higher the students' historical literacy and communicative rationality, the better their ability to understand, analyze, and respond to contemporary historical issues critically and argumentatively. The conclusion of this study is that strengthening historical literacy and developing communicative rationality in history learning plays a crucial role in shaping students' ability to respond to various contemporary historical issues reflectively, rationally, and responsibly.